1995
DOI: 10.1016/0166-1280(95)04155-y
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the structure of poly[di(phenoxy)thionylphosphazene]

Abstract: The stable structure of poly [(diphenoxy)thionylphosphazene] single chains was modeled with a small molecular compound consisting of one repeat unit of the polymer. The geometrical parameters of the nonplanar "trans-cis" conformations of these molecular models were obtained using the ab initio molecular orbital theory. The 3-21G* basis set was used in the computation. It was found that the phenoxy groups are positioned approximately parallel to the backbone and the groups located on adjacent phosphorus atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Unfortunately, such calculations are often hampered by “end-group” effects in which the HOMO and LUMO tend to be found at opposite ends of the polymer or short-chain oligomeric chain (Figure S11). This aspect has been noted in earlier calculations of inorganic polymers. ,, Despite these limitations, the calculated 7-monomer unit methyl-based oligomer suggests some electronic delocalization along the backbone, although the end-group effects are still noteworthy within the compounds examined from a theoretical perspective here (see Supporting Information, pp S-3 to S-15). This effect is also clearly denoted in a potential radical cation, in which the SOMO is delocalized over several atoms (Figure S13).…”
Section: Resultsmentioning
confidence: 55%
“…Unfortunately, such calculations are often hampered by “end-group” effects in which the HOMO and LUMO tend to be found at opposite ends of the polymer or short-chain oligomeric chain (Figure S11). This aspect has been noted in earlier calculations of inorganic polymers. ,, Despite these limitations, the calculated 7-monomer unit methyl-based oligomer suggests some electronic delocalization along the backbone, although the end-group effects are still noteworthy within the compounds examined from a theoretical perspective here (see Supporting Information, pp S-3 to S-15). This effect is also clearly denoted in a potential radical cation, in which the SOMO is delocalized over several atoms (Figure S13).…”
Section: Resultsmentioning
confidence: 55%
“…In the last decades, computational methods have become important for studying the properties of molecules. Previous ab initio quantum chemical studies on the structure and bonding of cyclic and short chain linear phosphazene molecules were carried out by Trinquier , and Ferris et al , Subsequently we performed in our group quantum chemical calculations which focused on the structure and chain flexibility of linear, short chain thionylphosphazene molecules. In this paper, we want to study the molecular geometry and the electronic structure of the six membered phosphazene and heterophosphazene rings 1 − 3a − c and their cations 4 − 6a,b and the thermal stability of the neutral rings 1 − 3a − c with respect to the heterolytic cleavage of a ligand with ab initio molecular orbital calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(thionylphosphazenes) [(NSOX)(NPCl 2 ) 2 ] n (PTPs) are a new class of inorganic polymers that possess a backbone of sulfur(VI), nitrogen, and phosphorus atoms (see Figure ). These materials can be regarded as hybrids of poly(oxothiazenes) [RS(O)N] n and poly(phosphazenes) [R 2 PN] n . , Synthesis and the thermal analysis of PTPs were first reported by Manners and co-workers. , In previous papers we reported on the molecular geometry and torsional mobility of PTP backbones with different substituents bonded to phosphorus and sulfur. , We used molecular orbital ab initio calculations on model compounds for these studies. The calculations on the halogenated molecules (chlorine bonded to phosphorus, and fluorine or chlorine bonded to sulfur) showed that the main chain of the fluorinated molecule (X = F) is more flexible than the backbone of the chlorinated molecule (X = Cl).…”
Section: Introductionmentioning
confidence: 99%